Pyroxenites and Megacrysts From Alkaline Melts of the Calatrava Volcanic Field (Central Spain): Inferences From Trace Element Geochemistry and Sr-Nd Isotope Composition - Villaseca, Carlos; García Serrano, Javier; Orejana, David (Frontiers in Earth Science, 2020)
Alkaline volcanic rocks from explosive monogenetic centres often carry an unusual cargo of crystals and rock fragments, which may provide valuable constraints on magma source, ascent and eruption. One of such examples is the Cenozoic Calatrava Volcanic Field in central Spain, a still poorly explored area to address these issues. Clinopyroxene, amphibole and phlogopite appear either as megacryst/phenocrysts or forming fine-grained cumulates (pyroxenite enclaves s.l.) in some eruptive centres of this volcanic field. They have previously been interpreted as cogenetic high-P minerals formed within the upper lithospheric mantle. Nevertheless, the presence of Fe-Na-rich green and Mg-Cr-rich colourless clinopyroxene types as phenocryst cores or as oscillatory zoned crystals in pyroxenite enclaves points to a complex evolution of mineral fractionates from petrogenetically related magmas. In trace element chemistry all studied clinopyroxene types show parallel rare earth element patterns irrespective of whether they are megacrysts, colourless or green core phenocrysts, or zoned crystals within pyroxenite cumulates. This similarity indicates a genetic relationship between all the fractionated minerals. This is in agreement with the overlapping of initial 143Nd/144Nd and 87Sr/86Sr ratios of pyroxenite enclaves (0.512793-0.512885 and 0.703268-0.703778) that is within the chemical field of the host magmas and the Calatrava volcanics. The initial 143Nd/144Nd and 87Sr/86Sr ratios of megacrystic clinopyroxene, amphibole and phlogopite show a more restricted range (0.512832–0.512890 and 0.703217–0.703466), also falling within the isotopic composition of the Calatrava volcanic rocks. Deep magmatic systems beneath monogenetic volcanic fields involve several stages of melt accumulation, fractionation and contamination at variable depths. Trace element and isotope mineral chemistry are powerful tools to understand the history of ascent and stagnation of alkaline basaltic magmas and discriminate between magma mixing, wall-rock contamination and closed magmatic system evolution. In our study, we establish a cogenetic origin for green and colourless clinopyroxene as high-pressure precipitates from liquids of different fractionation degrees (up to 80%, for the highly evolved melts equilibrated with the green clinopyroxene), originated from a highly solidified front of silica-undersaturated alkaline magmas at mantle reservoirs.